Optimizing yield and economic returns of rain-fed potato (Solanum tuberosum L.) through water conservation under potato-legume intercropping systems - Gitari, H.I.; Gachene, C.K.K.; Kamau, S.; Nyawade, S.; Sharma, K.; Schulte-Geldermann, Elmar; Karanja, N. (Elsevier, 2018)
Even though potato (Solanum tuberosum L.)-based intercropping systems are widely practised in developing countries, only a few studies have focused on legumes as the companion intercrops. This study was conducted to assess the effect of incorporating legumes into the potato production system on ground cover, soil moisture content (SMC), tuber and legume yield, potato equivalent yield (PEY), gross and net income and benefit: cost ratio (BCR). The treatments comprised of pure potato stand (PS), potato-dolichos (Lablab purpureus L.) (PD), potato-garden pea (Pisum sativum L.) (PG) and potato-bean (Phaseolus vulgaris L.) (PB). Results indicated a significantly higher (69%) ground cover at tuber initiation stage in PD compared to 66% in PG and PB and 56% in PS. Similarly, the highest SMC values were recorded at tuber initiation stage: 230, 207, 201 and 188 mm m-1 in PD, PG, PB and PS, respectively. Fresh tuber yield was highest in PS (36 t ha-1) and PD (35 t ha-1) and lowest in PG (29 t ha-1). PEY was higher under intercropping than monocropping systems. Potato-dolichos was the most profitable intercropping system with a net income of US$ 9174 ha-1 and a BCR of 5.7 compared to PS (US$ 7436 ha-1) with a BCR of 5.1. The study showed that dolichos is a promising legume crop that could be integrated into potato cropping systems to improve CWP without compromising the tuber yield.